Design and optimization of navigation and guidance techniques for Mars pinpoint landing: Review and prospect. (October 2017) - Yu, Zhengshi; Cui, Pingyuan; Crassidis, John L.
Abstract: Future Mars landing missions will require the capability of precise landing at certain sites for specific scientific interests to gather more valuable scientific information. Autonomous navigation and guidance in the Mars approach, entry, descent, and landing (AEDL) phase plays an important role in fulfilling a pinpoint landing mission. This paper systematically summarizes the latest developments and current status of autonomous navigation and guidance designs for Mars landing missions. Firstly, the AEDL phase for Mars landing is analyzed, and several landmark Mars landing missions are reviewed. Based on the precision requirement, the technology challenges of autonomous navigation and guidance for Mars pinpoint landing are discussed. Then, recent developments of autonomous navigation design, which contain the navigation scheme and state estimation methods are summarized. Furthermore, the cutting-edge concept of navigation scheme optimization is also introduced, which may provide new ideas to the mission design. Next, the state-of-art guidance technologies of entry and powered descent phases are analyzed. The corresponding reachable and controllable set analysis, trajectory optimization, and advanced guidance methods are also revealed. Finally, aiming to support future Mars pinpoint landing missions, a comprehensive prospective for the development of autonomous navigation and guidance is presented.